Immune signaling and regulation in esophageal cancer. (29th September 2014) - Calpe, Silvia; Compare, Debora; Mari, Luigi; Nardone, Gerardo; Parikh, Kaushal
Abstract : The following, from the 12th OESO World Conference: Cancers of the Esophagus, includes commentaries on signaling pathways that can be targeted with immunotherapy; the role of micro‐RNAs in the immune response to esophageal cancer; and the association between obesity, the immune system, and esophageal adenocarcinoma.